Acúmulo e desaparecimento de forragem e variações na estrutura de pastos de capim-xaraés submetidos a intensidades de pastejo em lotação intermitente - Galzerano, Leandro [UNESP]; Malheiros, Euclides Braga [UNESP]; Raposo, Elisamara [UNESP]; Morgado, Eliane da Silva [UNESP]; Ruggieri, Ana Claudia [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The aim of this study was to evaluate the effects of residual leaf area index (rLAI), years of evaluation and grazing cycles on the accumulation and disappearance of forage, and changes in the pasture structure of xaraes palisadegrass submitted to grazing intensities and intermittent stocking in two summers. The experiment was carried out at the Faculdade de Ciencias Agrarias e Veterinaria of Unesp, Campus of Jaboticabal, SP and the intensities of grazing were defined by four rLAI: 0.8, 1.3, 1.8 and 2.3. When the canopy intercepted 95% of incident light, the animals were placed on the pasture for grazing and kept until the rLAI target has been reached. Pastures were grazed by non-lactating Holstein cows (Bos Taurus Taurus L.), using the technique of mob-stocking. It was evaluated the canopy height, accumulation, disappearance and morphological components of forage and rest period. Residual leaf area index from 1.3 to 1.8 are the best in the accumulation and disappearance of forage and pasture structure. It is observed variability of the accumulation and disappearance of forage and pasture structure for years of assessment and grazing cycles within each year.
Accumulation and disappearance of forage and changes in the pasture structure of xaraes palisadegrass subjected to grazing intensities and intermittent stocking
Keywords: Brachiaria; canopy height; Light interception; rest period; rLAI; Urochloa